O desligamento institucional de adolescentes: intervenção por meio da técnica expressiva Paisagem Psíquica: um enfoque junguiano - Leite, Sandro José da Silva (2019)
The present research aims at studying psychological support for adolescents, during the process of institutional detachment, through an intervention with an expressive technique. Its main objectives are to investigate expectations regarding the future and life satisfaction, to understand individual narratives through symbolic and imagistic processing of adolescents, using the expressive technique Psychic Landscape as an intervention instrument. Therefore, it is necessary to substantiate the technique with the study of quadrants, according to the theory of C.G. Jung. The instruments of measurement are the EEQFA and EMSVA scales, initial and final interviews and intervention process, with the application of the technique. The participants are 11 adolescents from Casas Lares and SAICAs*, aged 17 years and one month and 17 years and 11 months, of both sexes, in the process of institutional disengagement. The method used is mixed, with a sequential exploratory approach. Individual weekly encounters were held with each of the 11 adolescents, and three of these young people performed the complete procedure, including the application of the EEQFA and EMSVA scales, initial and final interviews and eight intervention sessions. The others did not complete the meetings for several reasons. Three case studies complement the information. After the intervention, the study of the quadrants pointed out some significant differences: those who attended the meetings presented more forms that indicate circulation around a center (spiral), as well as those that refer to introspection (vertical), and less forms of centralization and protection (circle) and of emphasis on corporeal and physical (lower right quadrant); those who did not attend all the meetings presented only increase in the spiral form. Considering the case studies, more elements were identified in the first meetings in relation to the last ones, indicating discrimination throughout the intervention. These indicatives of the expressive technique regarding a conscious - albeit partial - apprehension are allied to the results of the EMSVA instrument, with an increase in the scoring - without statistical verification - of life satisfaction dimensions, except for school. The reduction of scoring - without statistical verification - in relation to the expectation regarding the future (EEQFA) may be linked to the proximity of the detachment. The qualitative analysis in the case studies demonstrates that adolescents were able to express feelings, to express their imagination freely, to make plans to the future, as well as to reflect on possibilities and limitations in relation to life outside the institution, and to become aware of acts committed in the past, that which underlies the possibility of reorienting attitudes and behaviors. *Institutional shelter services for children and teenagers in Brazil